SEVEN TOOLS AS THE PROBLEM SOLVING WAYS T0 IMPROVE QUALITY CONTROL - Rachmasari Pramita Wardhani; Erwin Gustianta (Mechanical Engineering Departement - Universitas Tridharma, 2021)
There are many ways for the company to reach a good standard for their goods and services.Standard is essential to achieve a level of customer trust. The company must be maintaining the quality oftheir services and products, including in this case the quality of goods beside the services. To ensure itsachievement, a directed management system and processes are needed to achieve the level of customertrust. Many companies use quality tools to help monitor and manage their quality system. There areseveral types of tools that can be used. But the more, there are seven management tools for qualitycontrol are the most common. Seven tools can be used by any professional to ease the quality improvement process like flowcharts, check sheets, Pareto diagrams, cause and effect diagrams,histograms, scatter diagrams, and control charts. Key words : seven tools, control, quality, problem solving